British economic growth, 1688-1959 : trends and structure - Deane, Phyllis; Cole, W. A. (Cambridge, Eng. : University Press, 1962)
The object of the inquiry which gave rise to this volume was to establish the main quantitative features of the British economy over as long a period as the available statistics world permit.
Includes index.
Includes bibliographical references: p. 335-341.
aia 10/05/2018
Loans
Keywords: Economic conditions--History; Great Britain